FAKTOR RISIKO KEJADIAN DROP OUT PENGGUNAAN ALAT KONTRASEPSI PADA WANITA PASANGAN USIA SUBUR DI WILAYAH KERJA PUSKESMAS MAPILLI - Andi Liliandriani; Urwatil Wusqa Abidin; Alfi Syahri Futri Diana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
Increasing drop out rates in contraceptive use can have an impact on population growth, which in turn affects welfare, quality of education, development and health, thereby reducing the quality of the population in a country. This study aims to identify risk factors that cause drop outs in contraceptive use among women of childbearing age (PUS) in the Mapilli Community Health Center area. The type of research used is analytical observational with a case control design. Samples were taken using the Lames How formula with a ratio of 1:1, and the total sample was 176 people. Data were analyzed using the chi square test and odds ratio test. The results of the study showed that there was a significant relationship between age (p=0.001) and the incidence of dropping out of contraceptive use, while knowledge (p=0.232), side effects (p=0.061) and husband's support (p=0.395) did not have a significant relationship with the incidence of drop out use of contraceptives in women of childbearing age in the working area of the Mapilli Health Center. Women at reproductive age who are classified as healthy have a tendency to experience drop outs (OR=5.051) or 5 times greater than women who are not reproductively healthy.